A tunable flexible pre-defined crack strain sensor and a method of manufacturing the same
Patent Information
- Application Number
- CN202611162463.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-16
AI Technical Summary
[0006]鉴于上述的分析,本发明实施例旨在提供一种可调控的柔性预定义裂纹应变传感器,用以解决现有技术中柔性传感器灵敏度低、线性传感范围窄、易失效、灵敏度和线性传感范围不可控的问题
[0018]与现有技术相比,本发明至少可实现如下有益效果之一:
Smart Images

Figure CN122920972A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of flexible sensor technology, and more particularly to an adjustable flexible predefined crack strain sensor. Background Technology
[0002] Flexible sensors utilize flexible substrate materials (such as polyimide (PI), PET, PDMS, textiles, and ultra-thin metal foil) that can be bent, stretched, rolled, and even folded to adapt to curved or irregular surfaces. Compared to traditional rigid sensors, flexible sensors can adhere to skin, joint folds, and torso curves, conforming well to the human body's contours; they can deform synchronously with the stretching, bending, and twisting of bones / muscles, providing lag-free motion capture and excellent deformation synchronization; they are lightweight, thin, and flexible, and can be made into patches, fabrics, or tattoo-like films, making them suitable for wearable and long-term wear monitoring.
[0003] Sensors used in different parts of the human body require sensitivity and linearity ranges that match the signal amplitude, stress level, motion amplitude, and sensing accuracy requirements of that area. For example, the micro-signal areas of the fingertips / face / head require ultra-high sensitivity and narrow linearity; the dynamic areas of joints / trunk / limbs require medium-to-high sensitivity and medium-wide linearity; and the high-stress areas of the soles of the feet / buttocks require low sensitivity and ultra-wide linearity. Therefore, in the fabrication of flexible sensors, it is necessary not only to improve the compliance and robustness of the sensors through material selection and structural design, but also to achieve a balance between sensitivity and linear strain range based on the application area of the human body, in order to meet the requirements of different parts of the human body and improve the practical application value of the sensors.
[0004] In different application scenarios, it is difficult to achieve a balance between various sensor properties such as high sensitivity (gauge factor, GF), wide strain range, high linearity, high compliance and high robustness. The balance between sensitivity and linear sensing range is even more difficult to control.
[0005] Therefore, there is an urgent need for an adjustable, flexible, predefined crack strain sensor to achieve a balance between sensitivity and linear sensing range for different applications on different parts of the human body, thereby maximizing the practical application value of the sensor. Summary of the Invention
[0006] Based on the above analysis, the present invention aims to provide an adjustable flexible predefined crack strain sensor to solve the problems of low sensitivity, narrow linear sensing range, easy failure, and uncontrollable sensitivity and linear sensing range of existing flexible sensors.
[0007] On one hand, embodiments of the present invention provide an adjustable flexible predefined crack strain sensor, the sensor comprising a conductive sensitive layer and a substrate layer, wherein the conductive sensitive layer comprises a high-resistivity sensitive layer and a low-resistivity sensitive layer nested within the high-resistivity sensitive layer, the conductive sensitive layer having a curved serpentine crack passing through both the high-resistivity sensitive layer and the low-resistivity sensitive layer, wherein the linear strain range of the sensor is >5.90%.
[0008] Furthermore, the curved serpentine cracks are parallel to each other.
[0009] Furthermore, the radius of curvature of the curved serpentine crack is 3~14mm.
[0010] Furthermore, the interval between the curved serpentine cracks is 0.8~4.0 mm.
[0011] Furthermore, the length between the two ends of the curved serpentine crack accounts for 62.5% to 93.75% of the width of the conductive sensitive layer.
[0012] Furthermore, the serpentine crack penetrates the conductive sensitive layer in the depth direction and extends to the substrate layer, and the depth of the crack on the substrate layer accounts for 5% to 25% of the thickness of the substrate layer.
[0013] Furthermore, from top to bottom, the upper surface of the low-resistivity sensitive layer and the upper surface of the high-resistivity sensitive layer are located on the same plane.
[0014] Furthermore, the width ratio of the low-resistivity sensitive layer to the width of the high-resistivity sensitive layer is 0.3 to 0.7.
[0015] Furthermore, the substrate material constituting the conductive sensitive layer is the same as the material constituting the base layer.
[0016] Furthermore, the conductive sensitive layer also includes a conductive functional phase uniformly dispersed in the matrix material, wherein the content of the conductive functional phase in the low-resistivity sensitive layer is greater than 2-10% of the content in the high-resistivity sensitive layer.
[0017] On the other hand, embodiments of the present invention also provide a method for fabricating the aforementioned adjustable flexible predefined crack strain sensor, the method comprising the following steps: (1) Preparing the conductive sensitive layer, including preparing the low-resistivity sensitive layer and the high-resistivity sensitive layer; (2) The substrate layer is prepared on the high-resistivity sensitive layer; (3) Prepare the serpentine crack.
[0018] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects: 1. Compared with existing flexible strain sensors with microcrack structures, the conductive sensitive layer constituting the sensor of the present invention has a double-layer nested structure: a low-resistance sensitive layer and a high-resistance sensitive layer. During the process of applying tensile stress to the sensor, it can increase the degree of resistance change during the stretching process of the sensor, thereby significantly improving the sensitivity of the sensor. In addition, by adjusting the form of the predefined crack, the fracture mode of the crack during the stretching process of the sensor can be controlled, thereby realizing the change and balance between the sensor sensitivity and the linear sensing range, so as to meet the different requirements of different parts of the human body for the sensor performance.
[0019] 2. By adjusting the location and structural parameters of predefined cracks, including crack shape, crack spacing, length between the two ends of the crack, and crack depth, this invention can improve the sensor's sensitivity, broaden the strain range (linear sensing range), and balance sensitivity and sensing range, while also improving the sensor's cyclic stability and durability.
[0020] 3. This invention uses a polymer constituting the substrate material as the matrix material. By doping with different amounts of conductive nanoparticles, sensitive layer materials with different electrical conductivities are obtained. This can improve the thickness of each layer of the sensor and the bonding between each layer, thereby improving the compliance, robustness and cycle stability of the sensor and extending the service life of the sensor.
[0021] 4. The sensitivity of the sensor of this invention is ≥20000, reaching 3.5×10⁻⁶. 5 It can stably detect minute vibrations and strains (e.g., 0.667%, 0.267%, 0.200%, 0.067%); the strain range is ≥5.90%, reaching up to 19.52%; it has good linearity, R0 2 The sensitivity ranges from 0.90 to 0.99; it exhibits excellent cyclic stability, maintaining high sensitivity and linearity even after 11,000 cycles, making it suitable for long-term human activity monitoring.
[0022] In this invention, the above-described technical solutions can be combined with each other to achieve more preferred combinations. Other features and advantages of this invention will be set forth in the following description, and some advantages may become apparent from the description or be learned by practicing the invention. The objects and other advantages of this invention can be realized and obtained from what is particularly pointed out in the description and drawings. Attached Figure Description
[0023] The accompanying drawings are for illustrative purposes only and are not intended to limit the invention. Throughout the drawings, the same reference numerals denote the same parts.
[0024] Figure 1 is a schematic diagram of the shape of the serpentine crack penetrating the conductive sensitive layer in the sensor of the present invention; Figure 2 This describes the composition and structure of the sensor of the present invention; Figure 3 A schematic diagram of the propagation of the serpentine crack during the stretching process of the sensor of the present invention: (1) two-dimensional layer; (2) three-dimensional layer; Figure 4 The strain-relative resistance change response curves of the sensor of the present invention under different crack intervals are shown. Figure 5 The curve showing the change in resistance of the sensor of the present invention as a function of the length of the serpentine crack; Figure 6 This is a curve showing the change in the sensitivity coefficient of the sensor of the present invention with the width of the low-resistivity sensitive layer; Figure 7 The strain-resistance response curves of sensors with different crack shapes during the tensile process of this invention are shown. Figure 8 This is the strain-resistance response curve of the sensor during the stretching process of the present invention; Figure 9 The sensor of this invention exhibits its resistance response curve during cyclic loading under minute strain. Figure 10 This is the resistance response curve of the sensor during the cyclic loading process of the present invention; Figure 11 This is the strain-hysteresis response curve of the sensor during the stretching process in Embodiment 1 of the present invention; Figure 12 This is a flowchart illustrating the fabrication process of the sensor of the present invention.
[0025] Figure label: 1-Low-resistance sensitive layer; 2-High-resistance sensitive layer; 3-Base layer; 4-Serpentine crack; 5-Wire. Detailed Implementation
[0026] The preferred embodiments of the present invention will now be described in detail with reference to the accompanying drawings, which constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not intended to limit the scope of the present invention.
[0027] Flexible sensing technology, with its soft, thin, and stretchable characteristics, enables flexible stretchable strain sensors to fit well against the surface of objects. Wearable products made from these sensors play a significant role in physiological monitoring and motion tracking, and also have many applications in human-computer interface interaction and soft robotics, thus attracting widespread attention.
[0028] However, in different application scenarios, it is difficult to simultaneously achieve multiple performance characteristics of sensors, such as high sensitivity (gauge factor, GF), wide strain range, high linearity, high compliance, and high robustness. This has always been a major challenge for all flexible strain sensors. Furthermore, sensors used in different parts of the human body require sensitivity and linear range that match the signal amplitude, force level, motion amplitude, and sensing accuracy requirements of that location. For example, the micro-signal areas of the fingertips / face / head require ultra-high sensitivity and narrow linearity; the dynamic areas of joints / trunk / limbs require medium-to-high sensitivity and medium-wide linearity; and the high-force areas of the soles of the feet / hips require low sensitivity and ultra-wide linearity. Therefore, in the fabrication of flexible sensors, it is necessary not only to improve the compliance and robustness of the sensors through material selection and structural design, but also to achieve a balance between sensitivity and linear strain range based on the application location on the human body, in order to meet the requirements of different parts of the body and enhance the practical application value of the sensors.
[0029] Therefore, the present invention provides an adjustable flexible predefined crack strain sensor, the sensor comprising a conductive sensitive layer and a substrate layer, wherein the conductive sensitive layer comprises a high-resistivity sensitive layer and a low-resistivity sensitive layer nested within the high-resistivity sensitive layer, and the conductive sensitive layer has a curved serpentine crack that passes through both the high-resistivity sensitive layer and the low-resistivity sensitive layer simultaneously.
[0030] The main principle of this resistive crack strain sensor is the contact and disconnection mechanism of conductive sensitive layers with different resistivities. Without changing the length of the sensor itself, cracks of different shapes are generated at the conductive sensitive layer by predefined crack structures. When the entire film is stretched, the cracks in the conductive sensitive layer break, changing the conductive path and thus causing a change in resistance, increasing the resistance of the fully stretched sensor. The predefined crack disconnection mechanism during sensor stretching is as follows: Figure 3 As shown in (1) and (2) in the figure.
[0031] This invention controls the fracture mode of the crack during the sensor's tensile process by adjusting the form of a predefined crack, ensuring it is either linear or curved. Figure 1 As shown in (a), (b), and (c), this allows for changes in sensor performance parameters such as sensitivity and linear sensing range to meet the different performance requirements of different parts of the human body. Figure 1 (a) is a straight serpentine crack, while (b) and (c) are curved serpentine cracks with radii of curvature of 14 mm and 3 mm, respectively. Among them, the straight crack ( Figure 1 (a) Due to the rapid fracture process and drastic change in resistance, it possesses high sensitivity, such as Figure 8 , 9As shown, however, the linear sensing range is relatively low; the curved serpentine crack slows down the rate of fracture propagation (crack formation), thus improving the linear sensing range of the sensor and reducing the sensor's hysteresis (e.g., Figure 11 As shown), as the waves gradually become denser, that is, as the radius of curvature of the crack in the curve decreases, the linear sensing range of the sensor gradually increases (e.g., Figure 7 (As shown). This invention, by predefining the crack shape and adjusting the balance between sensor sensitivity and sensing range, can regulate the sensor for different tasks to adapt to the detection of different human physiological signals and motion information.
[0032] Compared with existing flexible strain sensors with microcrack structures, the conductive sensitive layer constituting the sensor of this invention has a double-layer nested structure: a low-resistance sensitive layer and a high-resistance sensitive layer. During the application of tensile stress to the sensor, as the length of the base layer increases, a predefined serpentine crack that simultaneously passes through the high-resistance sensitive layer and the low-resistance sensitive layer can gradually extend from the opening in both the length and depth directions. In the length direction, gaps are sequentially generated inside the high-resistance sensitive layer, the low-resistance sensitive layer, and the high-resistance sensitive layer, changing the current conduction path. On the one hand, the extended current conduction path can increase the resistance of the sensor; on the other hand, based on the resistivity difference between the high-resistance sensitive layer and the low-resistance sensitive layer, the degree of resistance change during the stretching process of the sensor can be further increased, thereby significantly improving the sensitivity of the sensor.
[0033] The crack breaking mechanism is explained in two dimensions from the top-down view of the sensor. When the sensor is not pulled apart, the conductive sensitive layer is in contact with each other, and the current flows through the sensor uniformly. As the length of the sensor substrate layer increases, a predefined crack opens from both sides of the sensor toward the center. At this time, the contact resistance between the cracks increases with the crack breaking, i.e., with the continuous increase of Lc. Since the resistivity of the low-resistivity region in the middle (e.g., 0.01 Ω·m for PDMS with 8 wt% carbon nanotube doping) and the resistivity of the high-resistivity regions on both sides (e.g., 378.92 Ω·m for PDMS with 2 wt% carbon nanotube doping) are significantly different, the overall resistance value of the sensor changes significantly as the crack gradually breaks.
[0034] This paper offers a three-dimensional explanation of the crack-breaking mechanism based on the cross-section of the sensor. Within the sensor's conductive sensitive layer, the high-resistivity sensitive layer is shaped like a concave "U," enclosing a low-resistivity sensitive layer, forming a double-nested structure. When the sensor is stretched, as the length of the PDMS substrate increases, the crack expands from top to bottom and from the outside inwards. The gaps between the sensitive layers open, increasing the contact resistance and further cutting the original conductive path, forcing current to flow only through the open crack. Due to the double-nested structure, even when the low-resistivity layer completely breaks, a portion of the high-resistivity layer remains connected at the bottom, forcing the current through the high-resistivity path, thus increasing the resistance change during stretching from a three-dimensional structural perspective.
[0035] The serpentine cracks described in this invention are parallel to each other. Setting the cracks to be parallel ensures a highly uniform stress distribution throughout the conductive sensing layer when the sensor is subjected to macroscopic axial tension. This parallel topology ensures that the crack opening displacement and fracture timing encountered by the current as it passes through each microcrack unit remain highly consistent. This allows the changes in the individual micro-tunneling resistances to be superimposed into a macroscopic total resistance signal in a highly regular linear manner. If the cracks are not parallel or intersect, extremely complex mixed-mode stress fields (such as shear stress interference) will be generated locally. This will not only lead to uncontrollable secondary random crack propagation or even local tearing of the substrate layer, but also cause severe nonlinear jumps and mechanical hysteresis in the resistance-strain response curve, reducing the repeatability and reliability of the sensor output signal.
[0036] It should be noted that, in order to achieve high detection sensitivity while broadening the linear strain range of the sensor and meeting the requirements of practical detection applications, the present invention needs to limit the curvature of the serpentine crack.
[0037] Specifically, the radius of curvature of the serpentine crack described in this invention is 3-14 mm, which can be 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, or 14 mm. If the radius of curvature of the serpentine crack is too small, the curvature at the crests and troughs will be too sharp, resulting in extreme local stress concentration at these extremely small curvature locations during tension. This not only easily induces irreversible plastic tearing or fatigue fracture of the PDMS matrix at the bottom, severely reducing the cycle life of the sensor, but also causes severe mechanical friction and adhesion on the crack surface when releasing strain, increasing the mechanical hysteresis of the sensor. If the radius of curvature is too large, the serpentine curve will tend to be flat, and its topological morphology will severely degenerate into an approximately straight crack. This causes the structure to lose its advantage of absorbing strain energy and delaying fracture through "geometric wave deformation (i.e., straightening process)," resulting in the crack being completely broken at extremely small strains. This greatly shortens the linear detection range of the sensor, making it unsuitable for large-strain applications such as large-scale human joint motion monitoring.
[0038] It should be noted that, in order to effectively improve the sensitivity of the sensor, simplify the preparation process and increase the yield, the present invention needs to control the distance between the curved serpentine cracks in the serpentine crack.
[0039] Specifically, the spacing range of the serpentine cracks is preferably 0.8~4.0 mm, and can be 0.8 mm, 1.0 mm, 1.2 mm, 1.5 mm, 1.8 mm, 2.0 mm, 2.2 mm, 2.5 mm, 2.8 mm, 2.9 mm, 3.0 mm, 3.3 mm, 3.5 mm, 3.7 mm, or 4.0 mm. Because the serpentine curve undergoes in-plane torsion, flattening, and lateral expansion during stretching, a larger lateral physical margin is required. If the crack spacing is too narrow (less than 2.0 mm), the local high stress fields of adjacent serpentine cracks will severely overlap and interfere, causing the edges of adjacent cracks to squeeze each other or even cross-adhere during stretching, preventing the cracks from separating cleanly and completely. This blocks the bypass effect of current transfer to the high-resistivity layer, resulting in a significant reduction in sensor performance. Figure 4 As shown, under the same conditions of other structural parameters and test conditions, the sensitivity and sensing range of the sensor decrease as the crack spacing increases.
[0040] It should be noted that, in order to improve the sensitivity of the sensor while taking into account stability and durability, the present invention needs to define the relative position and size of the crack.
[0041] It should be noted that, in order to improve the sensor's sensitivity while ensuring its robustness, the present invention needs to control the length of the curved serpentine crack in the serpentine crack.
[0042] Specifically, the length between the two endpoints of the straight line or curve accounts for 62.5% to 93.75% of the width of the conductive sensitive layer, and can be 62.5%, 63%, 65%, 67%, 68.5%, 70%, 72%, 75%, 77%, 79%, 81.25%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, or 93.75%. If the length is too short, it will reduce the sensitivity of the sensor; if the length is too long, it will lead to a decrease in the robustness of the sensor and make it more susceptible to damage. Figure 5 As shown, when the width of the conductive sensitive layer of the sensor is 20 mm, the sensor has excellent sensitivity only when the length between the two ends of the crack is greater than 12.5 mm.
[0043] According to a preferred embodiment of the present invention, when the width of the conductive sensitive layer of the sensor is 16 mm, the length between the two ends of the crack is within 13 to 15 mm, preferably 14 mm.
[0044] It should be noted that, in order to ensure that the preset crack in the conductive sensitive layer can be completely broken during the stretching process of the sensor and to effectively change the conductive path, the present invention needs to limit the depth of the serpentine crack.
[0045] Specifically, the depth of the serpentine crack is greater than the thickness of the conductive sensitive layer and less than the sum of the thicknesses of the conductive sensitive layer and the substrate layer. If the depth is less than or equal to the thickness of the conductive sensitive layer, the predefined serpentine crack in the conductive sensitive layer may not be effectively separated during the stretching process of the sensor, failing to effectively change the conductive path, affecting the magnitude of the sensor's resistance change, and impacting the improvement of detection sensitivity and the widening of the linear sensing range. If the depth is too large, irreversible damage to the sensor may occur during the application of large tensile stress, affecting the sensor's cyclic stability and durability.
[0046] Specifically, the crack depth extending into the substrate layer should account for 5% to 25% of the total substrate layer thickness, i.e., the ratio of crack depth to substrate layer thickness should be 0.05:1 to 0.25:1. If the crack extension depth is too small (less than 5% or does not damage the substrate): the tolerance of the cutting process will be extremely low, making it difficult to ensure that the upper low-resistivity sensitive layer is completely and physically severed in actual manufacturing; if there are tiny connections between the underlying layers, residual parallel conductive paths will be formed, severely weakening the impedance mismatch effect and causing a significant decrease in sensor sensitivity; at the same time, during stretching, the uncut crack tip is prone to lateral propagation along the interface between the sensitive layer and the substrate, causing severe interlayer delamination. If the crack extension depth is too large (greater than 20%): the crack tip will introduce extremely severe stress concentration inside the PDMS elastic substrate; when the sensor is subjected to repeated high-strain stretching (such as joint bending), the crack tip will rapidly tear downwards, causing catastrophic mechanical fracture of the entire substrate, greatly shortening the sensor's cycle life and maximum elongation at break.
[0047] It should be noted that, in order to improve the durability of the sensor, the present invention embeds the low-resistivity sensitive layer of the conductive sensitive layer into the high-resistivity sensitive layer. Compared with the structure in which the low-resistivity sensitive layer and the high-resistivity sensitive layer are stacked one on top of the other, the low-resistivity sensitive layer and the high-resistivity sensitive layer in the double-layer nested structure have a higher bonding strength and are more durable in practical applications.
[0048] It should be noted that the low-resistance resistive layer of the present invention can be partially or completely embedded in the high-resistance resistive layer, that is, the surface of the low-resistance resistive layer can be higher or lower than the surface of the high-resistance resistive layer.
[0049] Preferably, the conductive sensitive layer of the present invention has a double-layer nested structure, and the upper surface of the low-resistivity sensitive layer and the upper surface of the high-resistivity sensitive layer are located on the same plane. In actual preparation and use, this simplifies the preparation process and improves the wear resistance of the sensor. In the preferred embodiment of the present invention, the position of the low-resistivity sensitive layer on the high-resistivity sensitive layer must be centered (i.e., symmetrical). Although extremely small processing tolerances are allowed in actual manufacturing processes, the macroscopic design should strictly avoid significant left or right deviations. The effect of non-centering: If the low-resistivity sensitive layer is severely offset, it will cause the width and thickness of the "sidewalls" (i.e., electrical bypasses) formed on the left and right sides of the U-shaped high-resistivity sensitive layer at the bottom to be severely asymmetrical. When the sensor is stretched and the central low-resistivity core breaks, the current instantly rushes to the bypass on the side with lower resistance, resulting in a severe current congestion effect. This will cause an extreme imbalance in the internal electric field and stress distribution, causing the electrical signal to fluctuate violently and drift the baseline when the sensor is subjected to even extremely slight torsion or non-axial force interference, completely destroying the stability based on the "bilateral symmetrical impedance mismatch" design.
[0050] It should be noted that the width of the intermediate low-resistance layer controls the basic trade-off between the initial resistance and the saturation resistance. As the width of the intermediate low-resistance layer increases, the initial resistance decreases, thus improving sensitivity. When the intermediate width exceeds a critical threshold, a current shunting effect occurs, and the widened low-resistance region spatially overlaps with the high-stress bottleneck region, leading to a decrease in the overall performance of the sensor. Therefore, in order to balance the initial resistance and the saturation resistance, this invention needs to control the relative width of the low-resistance sensitive layer and the high-resistance sensitive layer.
[0051] Specifically, the width ratio of the low-resistivity sensitive layer to the high-resistivity sensitive layer is (0.3~0.7):1, which can be 0.3:1, 0.4:1, 0.5:1, 0.6:1, or 0.7:1. If the width ratio is too small, the initial resistance of the sensor in its unstretched state will be too high. On the one hand, the excessively high base impedance can easily exceed the measurement range of conventional portable signal acquisition devices. On the other hand, the extremely narrow low-resistivity core channel will generate huge electrical signal fluctuations under slight disturbances, causing the sensor's signal-to-noise ratio to drop sharply and the baseline to become extremely unstable. If the width ratio is too large, the macroscopic electrical bypass mechanism will be severely weakened. On the one hand, an excessively wide low-resistivity layer means that an extremely long (and extremely deep) physical crack is needed to completely sever it, which will overlap with the high-stress bottleneck area of the material, reducing the overall stability of the structure. On the other hand, when the excessively wide low-resistivity channel is stretched and cracked, the current can still find a relatively wide low-resistivity residual path, making it difficult to be instantly "forced" into the high-resistivity sensitive layers on both sides. This results in a slower slope of the overall impedance change with strain, thus significantly reducing the sensor's ultra-high sensitivity under small strains. Figure 6As shown, under the same conditions of other structural parameters and test conditions, when the low-resistivity sensitive layer is too narrow or too wide compared to the high-resistivity sensitive layer, it is not conducive to improving the sensor sensitivity.
[0052] Preferably, the width of the low-resistivity sensitive layer is equal to 1 / 2 of the width of the high-resistivity sensitive layer.
[0053] This invention not only predefines the crack, but also improves the sensor's cyclic stability and durability by adjusting other performance parameters of the serpentine crack, such as the length of the serpentine crack segment, the crack interval, the length between the two ends of the crack, the crack depth, and the structure of the conductive sensitive layer.
[0054] It should be noted that, in order to improve the linearity or stability of the sensor, the present invention needs to define the position of the low-resistivity sensitive layer.
[0055] Specifically, the low-resistivity sensitive layer is nested in the high-resistivity sensitive layer in a centered manner.
[0056] It should be noted that, in order to increase the thickness of each layer of the sensor and the bonding between the layers, improve the sensor's compliance, robustness and cycle stability, and extend the sensor's service life, this invention needs to limit the constituent materials of the base layer and the functional layer.
[0057] Specifically, the substrate material constituting the conductive sensitive layer is the same as the material constituting the base layer.
[0058] More specifically, the material constituting the base layer of the present invention can be a silicone rubber elastomer, a thermoplastic polymer, or a porous sponge material, such as at least one of polydimethylsiloxane, Ecoflex series, Dragon Skin series, thermoplastic polyurethane, styrene-ethylene-butene-styrene block copolymer, natural rubber, or hydrogel, which serves to provide the sensor with the required flexibility, stretchability, and structural support.
[0059] According to a preferred embodiment of the present invention, the material constituting the substrate layer is PDMS.
[0060] Specifically, the conductive sensing layer further includes a conductive functional phase uniformly dispersed in the matrix material, wherein the content of the conductive functional phase in the low-resistivity sensing layer is greater than the content in the high-resistivity sensing layer.
[0061] More specifically, the conductive functional phase material constituting the conductive sensitive layer of the present invention can be carbon material, metal material, or conductive polymer, and its function is to convert mechanical deformation into a resistance change signal.
[0062] More specifically, the conductive functional phase is at least one of carbon black, carbon nanotubes, graphene and its derivatives, metals, and conductive polymers.
[0063] The conductive sensing layer of this invention employs a conductive polymer composite material, specifically a composite material in which conductive particles are doped into a flexible, stretchable insulating matrix material. The matrix material provides flexibility and elasticity, while the conductive particles form a conductive network. When the sensor is stretched or bent, the distance between the conductive particles changes, or the conductive pathway is disrupted, thereby generating a resistance change signal.
[0064] According to a preferred embodiment of the present invention, PDMS is used as the matrix material of the conductive sensitive layer. By adding conductive particles (such as carbon nanotubes) of different masses to PDMS, sensitive layer materials with different resistivities are obtained. A double-layer structure of the conductive sensitive layer is realized by simple preparation methods such as scraping, transfer printing, and mechanical cutting of customized shapes, so as to aggravate the change in resistance of the sensitive layer before and after stretching.
[0065] This invention alters the amount of conductive particles added to the conductive sensitive layer, thereby changing the resistivity of different parts of the conductive sensitive layer using a single sensitive layer material, and further amplifies the resistance change of the sensor during the stretching process.
[0066] More specifically, the content of the conductive functional phase in the conductive sensitive layer is 1.5% to 12% by mass percentage. A higher amount of conductive functional phase results in lower resistivity and lower resistance for the same area. However, excessive doping with conductive functional phase diminishes the resistivity reduction and decreases the toughness of the elastomer composite material, increasing brittleness and hardness. This leads to a decrease in the tensile strength and elongation at break of the sensor, affecting its compliance and durability. Therefore, this invention limits the conductive functional phase to 1.5% to 12% of the mass of the elastic matrix material, which can be 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, or 12%.
[0067] It should be noted that, in order to improve the detection sensitivity of the sensor, the present invention requires that the amount of conductive functional phase added in the low-resistivity sensing layer be greater than the amount added in the high-resistivity sensing layer.
[0068] More specifically, the conductive functional phase in the low-resistivity sensing layer accounts for 7 to 12% of the mass of the elastic matrix material, which can be 7%, 8%, 9%, 10%, 11%, or 12%.
[0069] More specifically, the electrically functional phase in the high-resistivity sensing layer accounts for 1.5 to 5% of the mass of the elastic matrix material, which can be 1.5%, 2%, 3%, 4%, or 5%.
[0070] It should be noted that, in order to improve the sensor's sensitivity while ensuring its compliance and robustness, this invention requires limiting the structural thickness of each layer of the sensor.
[0071] Specifically, the thickness of the conductive sensitive layer is 70~400 μm, and can be 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 200 μm, 230 μm, 150 μm, 170 μm, 200 μm, 230 μm, 250 μm, 280 μm, 300 μm, 320 μm, 350 μm, etc. If the thickness of the conductive sensitive layer is too thick, it can easily lead to an increase in the overall stiffness of the conductive sensitive layer, reducing the flexibility of the sensor. At the same time, it can make it difficult for cracks to penetrate completely longitudinally or cause strain transmission to lag, thereby significantly reducing the sensitivity and response speed of the sensor. If the thickness of the sensitive layer is too thin, it can easily lead to an overly sparse conductive path, unstable initial resistance, and is prone to overall fracture during stretching, making it impossible to form a uniform and controllable 3D crack network, which seriously weakens the robustness of the sensor.
[0072] Specifically, the thickness of the substrate layer is 0.5~3 mm, and can be 0.5 mm, 0.8 mm, 1.0 mm, 1.2 mm, 1.5 mm, 1.8 mm, 2.0 mm, 2.3 mm, 2.5 mm, 2.7 mm, or 3.0 mm. If the thickness of the substrate layer is too small, it will affect the overall mechanical support strength. When subjected to the intense stretching caused by the movement of large joints of the human body (such as elbows and knees), the substrate is very prone to local non-uniform deformation or tearing, and cannot effectively constrain the strain distribution of the sensitive layer. If the thickness is too large, it will affect the flexibility and fit of the sensor, increase the mechanical stress hysteresis of the device, and cause the sensor's ability to sense small physiological signals (such as pulse and swallowing) to be severely reduced.
[0073] It should be noted that, in order to ensure the high sensitivity and robustness of the sensor, the present invention also needs to define the thickness of the low-resistivity sensitive layer and the high-resistivity sensitive layer constituting the conductive sensitive layer.
[0074] More specifically, the thickness of the low-resistivity sensitive layer is 20~80 μm, which can be 20 μm, 40 μm, 55 μm, 60 μm, or 80 μm. If the thickness is too small, the conductive path will be too sparse, the initial resistance will be unstable, and the entire layer will be prone to breakage during stretching, making it impossible to form a uniform and controllable 3D crack network, which will seriously weaken the robustness of the sensor. If the thickness is too large, it will significantly increase the overall stiffness of the conductive sensitive layer, reduce the flexibility of the sensor, and make it difficult for cracks to penetrate completely longitudinally or cause strain transmission to lag, thereby greatly reducing the sensitivity and response speed of the sensor.
[0075] More specifically, the thickness of the high-resistivity sensitive layer is 50~300μm, and can be 50 μm, 80 μm, 100 μm, 120 μm, 140 μm, 165 μm, 190 μm, 220 μm, 250 μm, 280 μm, or 300 μm. If the thickness is too small, it will affect its ability to act as an electrical bypass when the low-resistivity sensitive layer cracks, and it is easy for it to break completely along with the low-resistivity sensitive layer, causing the sensor to lose its large strain detection range. If the thickness is too large, it will affect the macroscopic resistance change rate of the sensor. Because the volume of the high-resistivity layer is too large, it will have an excessively strong parallel current shunting effect, which will make the slope of the overall resistance increasing with strain slower, thereby reducing the sensitivity of the sensor under small strain.
[0076] Specifically, the sensor also includes conductive wires connected to the low-resistivity sensitive layer and the high-resistivity sensitive layer.
[0077] On the other hand, embodiments of the present invention also provide a method for fabricating an adjustable flexible predefined crack strain sensor, the method comprising the following steps: (1) Preparing the conductive sensitive layer, including preparing the low-resistivity sensitive layer and the high-resistivity sensitive layer; (2) The substrate layer is prepared on the high-resistivity sensitive layer; (3) Prepare the serpentine crack.
[0078] It should be noted that the method for preparing the conductive sensitive layer of the present invention can be surface attachment / transfer method, doping composite-integrated molding method, or 3D printing / additive manufacturing method.
[0079] According to some preferred embodiments of the present invention, a process flow diagram of a method for fabricating a high-sensitivity flexible predefined crack strain sensor is shown below. Figure 12 As shown, the specific steps include: S1: Adhesive tape is adhered to the bottom surface of the mold, and the adhesive tape is spaced apart; S2: Mixing an elastic matrix material with a conductive material yields two mixed solutions I and II. The resistivity of mixed solution I after curing is lower than that of mixed solution II after curing. S3: Apply the mixed solution I to the gaps in the tape and cure it to obtain the low-resistivity sensitive layer of the sensor; S4: The mixed solution II is scraped onto the mold after the low-resistivity sensitive layer is covered, and cured to obtain the high-resistivity sensitive layer of the sensor, wherein the high-resistivity sensitive layer and the low-resistivity sensitive layer constitute the conductive sensitive layer of the sensor; S5: The elastic matrix material is poured, cured, and demolded onto the conductive sensitive layer obtained in step S4 to obtain a sensor blank; S6: The sensor blank is mechanically cut to obtain a sensor with serpentine cracks on one side of the conductive sensitive layer.
[0080] Compared with other existing fabrication techniques for flexible sensors, this invention employs simple coating and casting processes to fabricate the sensor. Combined with conventional mechanical cutting, it improves the sensor's sensitivity, strain range, and linearity. Furthermore, by using two solutions of elastic matrix materials with different resistivities after curing to prepare a two-layer structure for the conductive sensitive layer, it not only improves the sensor's sensitivity, strain range, and linearity but also enables the sensor to be integrally molded, enhancing interlayer bonding strength and thus improving the device's robustness and durability. Moreover, the conductive elastic composite material used in this invention has a Young's modulus close to that of human tissue, enabling conformal contact, improving sensitivity and wearing comfort. Its stretchability and reversible deformation capabilities can withstand large strains such as joint movements, exhibiting strong compliance and long-term stability. This invention features a simple fabrication process, readily available raw materials, and low cost, meeting the needs of large-scale production.
[0081] It should be noted that, in order to improve the detection sensitivity of the sensor, the present invention needs to limit the shape, size and setting method of the adhesive tape adhering to the bottom surface of the mold.
[0082] Specifically, in step S1, the tape is curved. Depending on specific needs (such as applications on different parts of the human body), not only the mold shape can be designed, but also the shape of the tape can be designed to flexibly adjust the shape of the sensor to meet the application requirements of different parts of the human body or intelligent robots.
[0083] More specifically, in step S1, tape is spaced out on the bottom surface of the mold to facilitate subsequent processes and obtain a double-layer structure of the conductive sensitive layer of the sensor, thereby improving the detection sensitivity of the sensor.
[0084] It should be noted that, in order to improve the sensitivity of the sensor detection and ensure other performance of the sensor, the present invention needs to define the relationship between the spacing between adjacent tapes and the tape width, so as to control the relative width of the low-resistivity sensitive layer and the high-resistivity sensitive layer constituting the conductive sensitive layer of the sensor.
[0085] Specifically, in step S1, the spacing between adjacent tapes is less than or equal to the width of the tape. The spacing between the tapes is the width of the subsequently prepared low-resistivity sensitive layer. The width of the tape and subsequent mechanical cutting determine the width of the high-resistivity sensitive layer. Therefore, limiting the relationship between the spacing between the tapes and the tape width not only allows for the adjustment of the relative positions of the low-resistivity sensitive layer and the high-resistivity sensitive layer, but also enables the control of their relative width, thereby achieving the regulation of the sensor's detection sensitivity and stability.
[0086] It should be noted that the shape and size of the sensor (such as width, thickness, and length) have a significant impact on human applications, affecting multiple dimensions such as wearing comfort, signal quality, biocompatibility, and long-term stability. The present invention adjusts the shape and size of the tape according to the actual application needs of the sensor.
[0087] Specifically, the thickness of the tape determines the thickness of the subsequently prepared low-resistivity sensitive layer, which is 20~100 μm, and can be 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, or 100 μm. If the thickness is too small, the conductive path will be too sparse, the initial resistance will be unstable, and it will be very easy to break completely during stretching, making it impossible to form a uniform and controllable 3D crack network, which will seriously weaken the robustness of the sensor. If the thickness is too large, it will significantly increase the overall stiffness of the conductive sensitive layer, reduce the flexibility of the sensor, and at the same time make it difficult for cracks to penetrate completely longitudinally or cause strain transmission to lag, thereby greatly reducing the sensitivity and response speed of the sensor.
[0088] It should be noted that, in order to improve the compliance and durability of the sensor, the present invention needs to limit the selection range of the elastic matrix material and the conductive functional phase.
[0089] Specifically, in step S2, the elastic matrix material is at least one of polydimethylsiloxane (PDMS), Ecoflex series, Dragon Skin series, thermoplastic polyurethane, styrene-ethylene-butene-styrene block copolymer, natural rubber, and hydrogel, preferably PDMS.
[0090] Specifically, the conductive functional phase is at least one of carbon black, carbon nanotubes (CNTs), graphene and its derivatives, metals, and conductive polymers, preferably CNTs.
[0091] It should be noted that, in order to ensure the sensor has high sensitivity strain sensing performance while preventing the material from becoming brittle and ensuring the toughness and processing performance of the matrix material, this invention needs to limit the amount of conductive functional phase added to the elastic matrix material.
[0092] Specifically, in step S2, the mixed solution I is used to prepare the low-resistivity sensitive layer of the sensor. The higher the amount of conductive functional phase added, the lower the resistivity and the lower the resistance under the same area. However, excessive doping of conductive functional phase will result in an insignificant decrease in resistivity. Moreover, the higher the content, the higher the viscosity of the conductive material formed, which is prone to agglomeration and uneven coating. This will reduce the toughness of the elastomer composite material, increase its brittleness and hardness, and lead to a decrease in the tensile strength and a sharp reduction in the elongation at break of the sensor, affecting the compliance and durability of the sensor. Therefore, the present invention limits the conductive functional phase to account for 7~12% of the mass of the elastic matrix material, which can be 7%, 8%, 9%, 10%, 11%, or 12%.
[0093] Specifically, in step S2, the mixed solution II is used to prepare the high-resistivity sensitive layer of the sensor. The lower the amount of conductive functional phase added, the higher the resistivity and the higher the resistance under the same area. However, too little conductive functional phase will affect the detection sensitivity and linear strain range of the sensor. Therefore, the present invention limits the conductive functional phase to 1.5~5% of the mass of the elastic matrix material, which can be 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, or 5%.
[0094] It should be noted that, in order to improve the detection sensitivity of the sensor, the present invention requires that the amount of conductive functional phase added in mixed solution I be greater than the amount added in mixed solution II.
[0095] It should be noted that, in order to improve the dispersion of conductive carbon particles in cured PDMS, the present invention mixes the conductive carbon particles with the PDMS prepolymer in a solvent. The solvent used in the present invention needs to have good CNT dispersion ability, good compatibility with the PDMS prepolymer, and a low boiling point. The solvent can be one of isopropanol (IPA), ethanol, acetone, toluene, etc., preferably isopropanol. The mass ratio of the solvent to the conductive carbon is 60:1 to 30:1 (e.g., 50:1). If too little solvent is added, the conductive carbon particles and PDMS prepolymer may not mix sufficiently, causing the conductive carbon particles to aggregate, increasing the bonding stress, and affecting the conductivity, flexibility, and deformability of the coil layer.
[0096] More specifically, in step S2, the conductive functional phase (such as CNT) is first added to the solvent (IPA) and uniformly dispersed to form a conductive carbon particle suspension, and then PDMS particles are added.
[0097] More specifically, the intensity of the ultrasonic treatment is 20-60kHz (e.g., 50kHz). If the ultrasonic frequency is too low, the cavitation effect is strong, the local energy is high, and the deagglomeration ability is strong. However, the energy is too concentrated and intense, which can easily lead to structural damage to CNTs (such as tube wall defects or fractures) and excessively shorten the length of CNTs. This will disrupt the continuity of the CNT conductive path and reduce the conductivity of the composite material. If the ultrasonic frequency is too high, the cavitation effect is milder and more uniform, reducing the damage to the CNT structure and helping to maintain the length and integrity of CNTs. However, the deagglomeration efficiency is relatively low, and a longer ultrasonic time may be required to achieve the ideal dispersion effect.
[0098] More specifically, the ultrasonic treatment time is 20-60 min (30 min). If the ultrasonic time is insufficient, the van der Waals forces will not be completely overcome, leaving CNT agglomerates, which will lead to poor electrical properties, an incomplete conductive network, and potentially poor mechanical properties, resulting in a decrease in material strength. If the ultrasonic time is too long, it may cause CNTs to break and shorten significantly. Shortened CNT length leads to the breakage of long-range conductive paths and a decrease in conductivity. At the same time, defects caused by excessive breakage may affect the interfacial bonding between CNTs and PDMS, and mechanical properties may be reduced.
[0099] It should be noted that, in order to avoid the re-agglomeration of conductive carbon, the present invention removes the solvent from the PDMS prepolymer mixture solution by mechanical stirring at a temperature above the solvent boiling point.
[0100] Specifically, in step S2, after adding the PDMS prepolymer to a suspension in which conductive carbon particles are uniformly dispersed, the suspension is mixed at a temperature of 60-100℃ (e.g., 80℃) with a stirring speed of 500-1500 rpm (1500 rpm). While ensuring uniform dispersion of the PDMS prepolymer, the solvent in the solution is evaporated, resulting in a prepolymer in which conductive carbon particles and PDMS prepolymer are uniformly dispersed and mixed. The temperature cannot be too high, otherwise the suspension will boil and splash, making it difficult to accurately control the mass ratio of PDMS to conductive carbon particles. It also cannot be too low, as this can lead to insufficient evaporation of isopropanol, and residual isopropanol will generate bubbles during the curing stage, affecting the integrity of the structure. If the mechanical stirring speed is too low, the solvent evaporation efficiency is low, and the conductive carbon particles in the high-viscosity PDMS may re-agglomerate due to sedimentation or insufficient Brownian motion, resulting in uneven dispersion of the conductive carbon particles. If the mechanical stirring rate is too high, the conductive carbon particle suspension may splash, leading to a loss of PDMS and conductive carbon particle content, making it difficult to accurately control the mass ratio of PDMS to conductive carbon particles.
[0101] It should be noted that, in order to control the thickness of the conductive sensitive layer, the present invention requires limiting the process conditions of two coating processes.
[0102] Specifically, in step S3, the coating process parameters for preparing the low-resistivity sensitive layer are: a gap of 50~150μm between the scraper and the mold substrate, a coating speed of 10~150 mm / s, and a scraper tilt angle of 45°~75°.
[0103] Specifically, in step S4, the coating process parameters for preparing the high-resistivity sensitive layer are: a gap of 70~400μm between the doctor blade and the aforementioned film, a coating speed of 10~150 mm / s, and a doctor blade tilt angle of 45°~75°.
[0104] It should be noted that, in order to improve the bonding strength between the conductive sensitive layer and the substrate layer of the sensor, simplify the fabrication process, and improve the compliance and robustness of the obtained sensor, the elastic material for preparing the substrate layer in this invention is limited to the elastic matrix material used for preparing the conductive sensitive layer.
[0105] Specifically, in step S5, the elastic matrix material is used to cast, cure, and demold onto the conductive sensitive layer obtained in step S4 to obtain a sensor blank, wherein the elastic matrix material is preferably PDMS.
[0106] It should be noted that, in order to improve the uniformity of curing of the elastic matrix composite material, enhance the mechanical properties of the material, and accelerate production efficiency, this invention requires limiting the curing temperature and time after scraping and casting.
[0107] Specifically, the curing temperature is 60~120℃, which can be 60℃, 70℃, 80℃, 90℃, 100℃, 110℃, or 120℃. If the curing temperature is too high, it will cause thermal degradation, thermal aging, or severe local thermal stress warping of the bottom elastomer substrate. In addition, the polymer matrix in the highly conductive slurry may be oxidized, which will damage the flexibility of the sensitive layer. If the curing temperature is too low, it will cause incomplete cross-linking of the polymer network of the double conductive sensitive layer and the substrate. The material will be in a semi-cured or sticky state with poor mechanical properties. Furthermore, due to the slow curing, the conductive nanomaterials (CNTs) will undergo secondary aggregation or uneven sedimentation under gravity.
[0108] Specifically, the curing time is 1 to 4 hours, which can be 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, or 4 hours. If the curing time is too long, the substrate and sensitive layer matrix will be over-cured and become brittle, which will greatly reduce the maximum tensile deformation range of the sensor and waste energy. If the curing temperature is too short, the degree of cross-linking will be insufficient. Not only will the sensitive layer be easy to detach from the substrate (interlayer peeling), but in subsequent tensile or destructive tests, permanent plastic deformation will easily occur inside the material, causing the sensor to produce huge hysteresis and irrecoverable zero-point drift.
[0109] It should be noted that, in order to further improve the detection sensitivity of the sensor, the present invention needs to control the specific process flow so that the low-resistivity sensitive layer in the sensor is nested inside the high-resistivity sensitive layer.
[0110] Specifically, in step S4, before applying the mixed solution II, the adhesive tape is removed to obtain a sensor cross-section as shown in Figure 1. Figure 3 As shown, the conductive sensing layer has a double-nested structure. By pre-setting cracks in this structure, when the sensor is subjected to external force and stretched, cracks fracture in both the two-dimensional and three-dimensional planes, maximizing the change in the overall resistance value of the sensor and thus maximizing its detection sensitivity.
[0111] It should be noted that, in order to improve the detection sensitivity and linearity of the sensor, the present invention requires the creation of cracks in the conductive sensitive layer of the sensor.
[0112] Specifically, in step S6, the sensor blank is mechanically cut to obtain a sensor with serpentine cracks on one side of the conductive sensitive layer.
[0113] More specifically, in step S6, the serpentine crack penetrates the conductive sensitive layer in the three-dimensional depth direction to maximize sensitivity and linear range during sensor use.
[0114] More specifically, in step S6, in the two-dimensional width direction, the width of the serpentine crack is greater than the width of the low-resistivity sensitive layer and less than the width of the high-resistivity sensitive layer, such as... Figure 3 As shown.
[0115] Preferably, the length between the two ends of the straight or curved serpentine crack accounts for 62.5% to 93.75% of the width of the conductive sensitive layer. It should be noted that the present invention controls the fracture mode of the crack during the sensor stretching process by controlling the process conditions of mechanical cutting and adjusting the shape of the serpentine crack. Figure 3 This allows for the adjustment of the balance between sensor sensitivity and linear sensing range according to different application needs.
[0116] According to some preferred embodiments of the present invention, the method for preparing a flexible crack strain sensor specifically includes the following steps: S1: Adhesive tape is adhered to the bottom surface of the mold and the tape is spaced apart, wherein the spacing between adjacent tapes (e.g., 5~12 mm) is less than or equal to the width of the tape (e.g., 16 mm). S2: Mix an elastic matrix material (such as PDMS) and a conductive functional phase (CNTs) to obtain two mixed solutions I and II; in mixed solution I, the conductive functional phase accounts for 7-12% of the mass of the elastic matrix material, and in mixed solution II, the conductive functional phase accounts for 1.5-5% of the mass of the elastic matrix material. The resistivity of mixed solution I after curing is lower than that of mixed solution II after curing. The specific mixing steps include: First, prepare a CNT / PDMS composite with a high CNT content of 7-12 wt% (e.g., 8 wt%). Add the CNT powder to the PDMS prepolymer according to a mass ratio of CNT powder to PDMS polymer of 7:93-3:22 (e.g., 2:23). The mass ratio of PDMS prepolymer to curing agent is 8:1-12:1 (e.g., 10:1). Add isopropyl alcohol (IPA) at a mass ratio of 60:1-30:1:1 (e.g., 50:1) to dissolve the CNT powder. Place the mixture on a heating table at 80-120°C (e.g., 90°C) and stir at 600-1000 rpm (e.g., 600 rpm) until all the isopropyl alcohol evaporates and the overall mass no longer changes. At this point, add the curing agent according to the specified ratio and stir thoroughly with a glass rod.
[0117] Next, prepare a CNT / PDMS composite with a lower CNT addition of 1.5~5wt% (e.g., 2 wt%). The mass ratio of CNT powder to PDMS polymer is 3:197~1:19 (e.g., 1:49). Follow the same process as for preparing a CNT composite with a higher CNT addition. S3: Using a PTFE scraper, uniformly apply the CNT / PDMS composite with a higher CNT content to the gaps in the PTFE groove mold where no transparent tape is pasted. Then, place the mold in an oven and heat it at 60~120℃ (80℃) for 1~4 h (e.g., 2 h) for high-temperature carbonization. After removing the mold, remove the pasted transparent tape to obtain a low-resistivity sensitive layer of the sensor with a thickness of 20~80μm. The scraping conditions include: a gap of 50~150μm between the scraper and the mold substrate, a scraping speed of 10~150 mm / s, and a scraper tilt angle of 45°~75°. S4: The CNT / PDMS composite with a lower CNT addition amount is coated into a PTFE groove mold in the same way to surround and cover the low-resistivity sensitive layer. The mold is then placed in an oven and heated at 80~120℃ (80℃) for 1~4h (e.g., 1h) to perform high-temperature carbonization, thereby obtaining a high-resistivity sensitive layer of the sensor with a thickness of 50~300μm. The coating conditions include: a gap of 70~400μm between the scraper and the aforementioned film, a coating speed of 10~150 mm / s, and a scraper tilt angle of 45°~75°. S5: Preparation of the base layer Mix the PDMS prepolymer and curing agent at a mass ratio of 10:1, and stir thoroughly at 800~1200 rpm (e.g. 1000 rpm) for 10~20 min (e.g. 15 min) to ensure thorough mixing. Then, perform vacuum degassing. Pour the resulting PDMS solution into a PTFE groove mold, allow it to stand to smooth the surface, and heat it at 80~120℃ (80℃) for 1~4 h (e.g. 3 h) to cure the PDMS substrate layer. Demold the mold to obtain the sensor blank. S6: Preparing serpentine cracks Use a mechanical cutter to cut the crack pattern according to the preset pattern (e.g.) Figure 1 As shown, the sensor blank is cut to obtain a sensor with a serpentine crack on one side of the conductive sensitive layer. In the three-dimensional depth direction, the serpentine crack penetrates the conductive sensitive layer. In the two-dimensional width direction, the width of the serpentine crack is greater than the width of the low-resistivity sensitive layer and less than the width of the high-resistivity sensitive layer.
[0118] Compared with existing spraying and dipping methods, the scraping (blade coating) process used in this invention precisely controls the coating thickness through blade gap and coating speed, resulting in better coating uniformity and stable film thickness. The wet film spreads evenly, and the adhesion between the functional layer and the flexible substrate is better after drying. Compared with existing screen printing and stencil replication, the coating obtained by scraping is thinner and has a smoother surface, requiring no custom molds and offering strong versatility for mass production. Compared with existing spin coating and inkjet printing, it can quickly achieve large-size film formation, making it suitable for large-scale production without being limited by the substrate area. Compared with precision deposition methods such as chemical vapor deposition (CVD), sputtering, and evaporation, the scraping process is simpler, requires less equipment, has higher raw material utilization, lower cost, and shorter cycle time. Furthermore, it has good adaptability to flexible substrates (PDMS, PET, fabrics, elastic films) and can be used with high-viscosity conductive pastes and composite functional coatings, with fewer formulation restrictions.
[0119] The sensor of this invention has a sensitivity ≥20000, reaching 3.5×10⁻⁶. 5 It can stably detect minute vibrations and strains (e.g., 0.667%, 0.267%, 0.200%, 0.067%); the strain range is ≥1.0%, reaching up to 19.52%; it has good linearity, R0 2 The sensitivity ranges from 0.90 to 0.99; it exhibits excellent cyclic stability, maintaining high sensitivity and linearity even after 11,000 cycles, making it suitable for long-term human activity monitoring.
[0120] The technical solution of the present invention will be further explained and illustrated below through specific embodiments and comparative examples.
[0121] Example 1 A flexible curved crack strain sensor and its fabrication method.
[0122] The sensor comprises an encapsulation layer and a functional layer. From top to bottom, the functional layer includes a substrate layer and a conductive sensing layer. The substrate layer is made of PDMS, with a width of 16 mm and a thickness of 1 mm. The conductive sensing layer has a double-layer nested structure, including a high-resistivity sensing layer 2 with a U-shaped structure and a low-resistivity sensing layer 1 embedded in the high-resistivity sensing layer structure. The high-resistivity sensing layer is PDMS doped with 2 wt% CNTs, with a thickness of 200 μm for the thicker part and 100 μm for the thinner part, and a width of 16 mm. The low-resistivity sensing layer is PDMS doped with 8 wt% CNTs, with a thickness of 100 μm and a width of 8 mm. The functional layer has straight serpentine cracks 4. From top to bottom, the serpentine cracks 4 penetrate the conductive sensitive layer and extend to the substrate layer, with a total depth Dc of 0.4 mm. From left to right, each serpentine crack 4 passes through both the high-resistivity sensitive layer 2 and the low-resistivity sensitive layer 1, with a length of 14 mm. The spacing between two adjacent serpentine cracks is 0.8 mm.
[0123] The preparation process flow diagram is as follows: Figure 12 As shown, it includes the following steps: (1) Preparation of conductive sensitive layer First, use 32mm wide transparent tape to stick inside the PTFE groove mold, and arrange them at intervals according to the predetermined width of the low resistance area in the middle of the sensor (8mm) to obtain a standard long strip conductive sensitive layer and a separation between two conductive sensitive layers with different resistivity. Fabrication of the conductive sensitive layer: First, a CNT / PDMS composite with a high CNT content of 8 wt% was prepared. The CNT powder was added to the PDMS prepolymer at a mass ratio of 2:23 (wherein the mass ratio of PDMS prepolymer to curing agent is 10:1), and isopropanol was added at a mass ratio of 50:1 to dissolve the CNT powder. The mixture was placed on a heating table at 90°C and stirred at 600 rpm until all the isopropanol evaporated and the overall mass no longer changed. At this point, the curing agent was added in proportion and stirred thoroughly with a glass rod. Next, a CNT / PDMS composite with a lower CNT addition of 2 wt% was prepared. The CNT powder to PDMS polymer was mixed at a mass ratio of 1:49, and the CNT / PDMS composite with a lower CNT addition was prepared using the same process as that for the higher CNT addition. Low-resistivity and high-resistivity conductive sensitive layers were prepared by a method of coating with a blade and then curing with heat. First, using a PTFE scraper, a CNT / PDMS composite with a high CNT content is evenly coated into the gaps of the PTFE groove mold where no transparent tape is attached. The specific conditions are: a 100μm gap between the scraper and the mold substrate, a scraping speed of 50mm / s, and a scraper inclination angle of 60°. Then, the mold is placed in an oven and heated at 80°C for 1 hour for high-temperature carbonization. After removing the mold, the attached transparent tape is removed to obtain a low-resistivity sensitive layer. Next, a CNT / PDMS composite with a lower CNT content is coated onto a PTFE groove mold using the same method to surround and cover the low-resistivity sensitive layer. The specific conditions are: film gap of 200 μm, coating speed of 50 mm / s, and doctor blade tilt angle of 60°. The mold is then placed in an oven and heated at 80°C for 1 hour to perform high-temperature carbonization to obtain a high-resistivity sensitive layer. (2) Preparation of the base layer The PDMS prepolymer and curing agent were mixed at a mass ratio of 10:1 and stirred thoroughly at 1000 rpm for 15 minutes. After thorough mixing, the mixture was degassed under vacuum. The resulting PDMS solution was poured into the high-resistance sensitive layer of the PTFE groove mold, allowed to stand to smooth the surface, and then heated at 80°C for 3 hours to cure the PDMS base layer. (3) Preparation of curved serpentine cracks The sensor film prepared in steps (1) and (2) is peeled off from the mold and cut using a mechanical cutter according to a preset curved crack pattern (e.g., Figure 1 (b) is shown) cut; a curved serpentine crack is prepared, wherein the radius of curvature of the curved serpentine crack is 3 mm and the interval is 0.8 mm.
[0124] Example 2 A flexible curved crack strain sensor and its fabrication method.
[0125] The same preparation method as in Example 1 was used, except that the radius of curvature of the curved serpentine crack obtained in step (3) was 14 mm and the interval distance was 1.0 mm.
[0126] Example 3 A flexible curved crack strain sensor and its fabrication method.
[0127] The same preparation method as in Example 1 was used, except that the radius of curvature of the curved serpentine crack obtained in step (3) was 10 mm and the interval distance was 2.0 mm.
[0128] Comparative Example 1 The same preparation method as in Example 1 was used, except that a straight serpentine crack was prepared in step (3).
[0129] Comparative Example 2 The same preparation method as in Example 3 was used, except that the interval distance in step (3) was 0.5 mm.
[0130] The structural and performance parameters of each embodiment and comparative example are shown in Table 1.
[0131] Table 1. Structural and performance parameters of the embodiments and comparative examples.
[0132] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.
Claims
1. An adjustable flexible predefined crack strain sensor, characterized in that, The sensor includes a conductive sensitive layer and a substrate layer. The conductive sensitive layer includes a high-resistivity sensitive layer and a low-resistivity sensitive layer nested within the high-resistivity sensitive layer. The conductive sensitive layer has a curved serpentine crack that passes through both the high-resistivity sensitive layer and the low-resistivity sensitive layer. The linear strain range of the sensor is >5.90%.
2. The sensor according to claim 1, characterized in that, The curved serpentine cracks are parallel to each other; And / or, the radius of curvature r of the curved serpentine crack is 3≤r≤14mm.
3. The sensor according to claim 1, characterized in that, The interval between the curved serpentine cracks is 0.8~4.0 mm.
4. The sensor according to claim 1, characterized in that, The length between the two ends of the curved serpentine crack accounts for 62.5% to 93.75% of the width of the conductive sensitive layer.
5. The sensor according to claim 1, characterized in that, The serpentine crack penetrates the conductive sensitive layer in the depth direction and extends to the substrate layer, and the depth of the crack in the substrate layer accounts for 5% to 25% of the thickness of the substrate layer.
6. The sensor according to claim 1, characterized in that, From top to bottom, the upper surface of the low-resistivity sensitive layer and the upper surface of the high-resistivity sensitive layer are located on the same plane.
7. The sensor according to claim 1, characterized in that, The width ratio of the low-resistivity sensitive layer to the width of the high-resistivity sensitive layer is 0.3 to 0.
7.
8. The sensor according to claim 1, characterized in that, The substrate material constituting the conductive sensitive layer is the same as the material constituting the base layer.
9. The sensor according to claim 8, characterized in that, The conductive sensitive layer further includes a conductive functional phase uniformly dispersed in the matrix material, wherein the content of the conductive functional phase in the low-resistivity sensitive layer is 2 to 10% greater than the content in the high-resistivity sensitive layer.
10. A method for fabricating an adjustable flexible predefined crack strain sensor according to any one of claims 1-9, characterized in that, The method includes the following steps: (1) Preparing the conductive sensitive layer, including preparing the low-resistivity sensitive layer and the high-resistivity sensitive layer; (2) The substrate layer is prepared on the high-resistivity sensitive layer; (3) Prepare the serpentine crack.